2010
DOI: 10.1186/1476-4598-9-240
|View full text |Cite
|
Sign up to set email alerts
|

t-DARPP regulates phosphatidylinositol-3-kinase-dependent cell growth in breast cancer

Abstract: BackgroundRecent reports have shown that t-DARPP (truncated isoform of DARPP-32) can mediate trastuzumab resistance in breast cancer cell models. In this study, we evaluated expression of t-DARPP in human primary breast tumors, and investigated the role of t-DARPP in regulating growth and proliferation in breast cancer cells.ResultsQuantitative real time RT-PCR analysis using primers specific for t-DARPP demonstrated overexpression of t-DARPP in 36% of breast cancers (13/36) as opposed to absent to very low t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 31 publications
0
66
0
Order By: Relevance
“…5 μm of TMA sections were used for IHC staining of AXL receptor tyrosine kinase with polyclonal goat AXL antibody (1:200) (AF154; R&D Systems). The intensity and frequency of staining were graded as described previously (28). …”
Section: Methodsmentioning
confidence: 99%
“…5 μm of TMA sections were used for IHC staining of AXL receptor tyrosine kinase with polyclonal goat AXL antibody (1:200) (AF154; R&D Systems). The intensity and frequency of staining were graded as described previously (28). …”
Section: Methodsmentioning
confidence: 99%
“…To measure cell proliferation, the Click-iT EdU Assay (Life Technologies) was performed following the manufacturer's recommendation, as previously described 15. EdU (5-ethynyl-2′-deoxyuridine) is a nucleoside analogue of thymidine and is incorporated into DNA during active DNA synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed using standard protocols 15. The protein concentration was determined by a Bio-Rad protein assay using a FLUO Star OPTIMA microplate reader (BMG).…”
Section: Methodsmentioning
confidence: 99%
“…t-DARPP is overexpressed in several malignancies, such as those of the stomach, colon, breast, and prostate (13-15). We and others have shown that t-DARPP protein promotes cell growth, survival, and drug resistance through activation of AKT signaling in cancer cells (14, 16-18). …”
Section: Introductionmentioning
confidence: 93%